Temporal-Lobe Epilepsy: Comparison of CT and MR Imaging - Schörner, W.; Meencke, H.-J.; Felix, R. (American Journal of Neuroradiology, 1987)
In 50 patients with temporal-lobe epilepsy, CT and MR findings were compared. Axial CT scans were obtained before and after administration of contrast material. Coronal MR imaging was carried out with two spin-echo (SE) sequences with a repetition time of 1600 msec and echo times of 35 or 70 msec (SE 1600/35, SE 1600/70). A focal lesion was detected by CT in 12 cases and by MR in 16 cases. If discrete attenuation or signal abnormalities are also taken into account, CT provided a positive finding in 13 cases and MR imaging in 20 cases. With the exception of a small calcification, all the lesions revealed on the CT scans were also detected on the MR images. Among the examinations assessable for temporal-lobe asymmetry, signs of a unilateral reduction in temporal-lobe size were seen on two of 35 CT scans and on 15 of 38 MR images. In three patients who had temporal-lobe resection, a subsequent comparison was made between CT, MR imaging, and pathology. Histologically proven glial reactions that could not be detected on CT were demonstrated as high-signal-intensity lesions on the SE 1600/70 image. We conclude that MR scanning, with its higher sensitivity, superior image quality, and ability of multiplanar imaging, should be the imaging technique of choice in the diagnosis of temporal-lobe epilepsy.